LIFESTYLE CHANGES AFTER BREAST CANCER SURGERY - AZEEZ, ZISTAN HUSSEIN; AHMED, SANA THANOON (Journal of Duhok University, 2023)
Background: Breast cancer is the most commonly diagnosed cancer in women worldwide, and it is also the second most significant cause of cancer death. Lifestyle is important to change among breast cancer women to prevent breast cancer recurrence and improve breast cancer prognosis. this study aims to explore the lifestyle changes of patients with breast cancer after surgery. Methods: A descriptive cross-sectional study design was directed to find out the change of lifestyle after breast cancer surgery among females who had breast cancer surgery in Duhok Governorate. The study was conducted on 110 patients who had breast cancer surgery in Duhok Governorate. Results: the mean age of the patients was (49.4 ± 10.1 SD) ranging from (30 to 71 years) and 75.5% were married, 57.3% were from urban, 86.4% were Muslim, 47.3% were illiterate, finally, 78.2% were unemployed. Sleep patterns of the patients have not changed after breast surgery and most of them were normal sleepers 62.7%. physical activity has reduced significantly (p-value= <0.0001) from preoperative to postoperative time. The study found that a significant improvement has been developed in the diet items of the patients, including increasing fruits and a reduction in creamy foods, sweet patisseries, soft drinks, and sugar-sweetened juices. Conclusion: the current study concluded that the lifestyle was not changed in physical activity and sleep. But a significant change in terms of diet was founded among patients after breast cancer surgery